Public policies and cartography of the traditional communities territory's on the coast of São Paulo and southern Rio de Janeiro - Freitas, Leonardo Esteves de [UNESP]; Sansolo, Davis Gruber [UNESP]; Cioffi, Giovana [UNESP] (Univ Federal Parana, Editora, 2024)
Official maps play a relevant role as representations of reality with specific objectives and, generally, favor hegemonic social actors. In contrast, researchers and communities have mapped elements of community interests, supporting the fight for their socio-territorial rights, as occurs in territories of traditional communities on the coast of S & atilde;o Paulo and south of Rio de Janeiro. This paper compares processes of spatial representation of these communities in nine official instruments of public territorial management and in two databases of partners of traditional communities in order to analyze the relationship between the representation of these communities and the incidence of public policy. Analysis parameters were defined to identify convergences and divergences between the materials: presence and absence of information; level of detail; way of characterizing communities. In official mappings, these communities are made invisible. Map maded by Laplan/Unesp shows 72 communities, against 23 of maps linked to public policies of the state of S & atilde;o Paulo, for the same territory. Map of Angra dos Reis and Paraty/RJ, prepared by Fiocruz/FCT, brings 82 communities, while official maps of the state of RJ present 42. Official maps highlight conservation units and urban and tourism activities and do not prioritize activities of traditional communities, subordinating traditional uses to the preservation of nature and the reproduction of capital. In practice, this leads to, the prohibition of activities that are essential for social reproduction, the criminalization of these communities and their disregard in the elaboration of public policies. Environmental policies and development vectors associated with the reproduction of capital are defined without considering the rights of these communities, which leads to sociocultural mischaracterization and the expulsion of community members from their territories, generating a worsening the socio-environmental situation.
Keywords: traditional communities; territorial conflicts; cartographic representations; public policy; coast